Behind–the–scenes: Aspects of a film reception. The case of The Independence of Romania (Aristide Demetriade, Grigore Brezeanu, 1912) and The Rest is Silence (Nae Caranfil, 2007) - Bruciu-Cozlean, Andra (Swedish Journal of Romanian Studies, 2024)
The foreign reader and viewer can find nothing better -or faster, given the exigencies of modern life- than the film as an introduction to the character, history, identity of a nation. With the awards garnered by directors like Cristian Mungiu and Nae Caranfil, new interest has been focused on Romania’s film, community, and history. That is why, an investigation regarding the Romanian early cinema would be necessary in the field of improving education from abroad. The purpose of this paper is to analyze a number of aspects, such as the importance of incorporating a course on cinema in foreign language teaching, one of the major goals being the opportunity to educate the students in the field of movies and thus offering them distinct cultural perspectives. However, this article does not plea for the need of a pedagogy of media studies in higher education, given the complexity of the topic. It rather aims to focus on the history of two Romanian movies: The Independence of Romania (1912) and The Rest is Silence (2007) and highlight the reasons why an urban icon of the city of Tampere is called “Plevna”. This paper sets out to analyze the two mentioned Romanian films who proved to be interesting for Finnish students since they depict an episode of our common history, the 1877 War of Independence (The Russo-Turkish War). At the same time, the paper aims to familiarize them with the allure of the event when Romanian and Finnish soldiers fought shoulder to shoulder on the same front, at Plevna. The Romanian film, The Independence of Romania shot in 1911-1912, was the first feature film to be kept almost entirely in the Romanian National Film Archive; the other one, The Rest Is Silence directed by Nae Caranfil (and representing Romania’s first entry into the 2009 Oscars) and inspired by The Independence of Romania wanted to show the real story of our first full-length filmmaking. Therefore, this latter film contains like a palimpsest an older mute movie, discovered in Romanian Movie Archive. The current article draws upon the insights provided by the Finnish students after watching the two films and summarizes their conclusions. In other words, these lines provide a behind-the-scenes glimpse of what they learned and discovered. The films were met with positive reviews, and we tried to follow the students’ spontaneous reactions and emotions. An important part of our work was to put in perspective the two inspiring patriotic marches which are commemorating the departure of the Romanian and Finnish soldiers at Plevna in the Balkan’s theater of War: Drum bun! (farewell song composed by Ştefan Nosievich to the lyrics of Romanian patriot Vasile Alecsandri) and Kauan on Kärsitty / Long have suffered, a well-known patriotic song of the Finnish Guard (Suomen kaarti). This article tangentially discusses the role of perception in educational activity, which is presented under two correlated aspects, namely: the activity carried out in this sense by the teacher and by the students and the role of cinema in creating cultural memory from a general perspective, in a way that transforms the manner we think of film and its social importance. This article starts from a very particular point of view, as we discovered by pure chance the name of Plevna building in Tampere, and goes to a more general aspect, which is the battle of Plevna, one of the most important episodes from Romania’s modern history.